Proceedings of the 2012 ACM Symposium on Document Engineering 2012
DOI: 10.1145/2361354.2361375
|View full text |Cite
|
Sign up to set email alerts
|

XML query-update independence analysis revisited

Abstract: XML transformations can be resource-costly in particular when applied to very large XML documents and document sets. Those transformations usually involve lots of XPath queries and may not need to be entirely re-executed following an update of the input document. In this context, a given query is said to be independent of a given update if, for any XML document, the results of the query are not affected by the update. We revisit Benedikt and Cheney's framework for query-update independence analysis and show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This technique was used by Robertson and Walker [233] to enhance the Okapi BM25 ranking function [234]. Some other approaches for query reformulation are utilization of structured query [69,219,141,127], Boolean query [213,173,107,144], XML query [138,65,137] and phrase matching [14].…”
Section: Query Reformulationmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique was used by Robertson and Walker [233] to enhance the Okapi BM25 ranking function [234]. Some other approaches for query reformulation are utilization of structured query [69,219,141,127], Boolean query [213,173,107,144], XML query [138,65,137] and phrase matching [14].…”
Section: Query Reformulationmentioning
confidence: 99%
“…The authors compared this technique to contemporary QE techniques and experimentally demonstrated the formers' superiority. XML queries can also be used for improving precision in IR systems for enhancing the Internet searches (e.g., [138,65,137]). Improving precision in IR systems through QE using web pages has been proposed by Cui et al [76,77] and Zhou et al [300].…”
Section: Importance Of Query Expansionmentioning
confidence: 99%
“…We formalized the notion of query-update independence and made this notion more precise and more general. Outside the SPARQL context, the query-update independence problem has been intensively studied, in particular in the relational context [3,10] and in the setting of XML structures [2,8]. However, due to the SPARQL/RDF's open world assumption, these results do not transfer to the SPARQL context.…”
Section: Related Workmentioning
confidence: 99%